Artificial leather and its manufacturing method
Patent Information
- Application Number
- JP2020149754
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-07
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-09-07
AI Technical Summary
【0012】 本発明の人工皮革によれば、摩擦や揉みに対する繊維脱落が少なく、特に洗濯機による水洗を行った場合でも、外観や物性の低下が少ない人工皮革を得ることができる。さらに、本発明の人工皮革は、天然皮革調の優美な外観と柔軟な触感を有しており、家具、椅子および車両内装材から衣料用途まで幅広く用いることができるが、特にその手入れのしやすさの観点から、衣料用途に好適に用いられるものである。
Smart Images

Figure 0007631708000001 
Figure 0007631708000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an artificial leather comprising a fiber-entangled body in which a woven fabric is integrally entangled with a nonwoven fabric made of ultrafine fibers and a polymeric elastomer, and which is less susceptible to fiber shedding due to friction or rubbing. [Background technology]
[0002] Natural leather-like artificial leather, which is mainly composed of a nonwoven fabric made of ultrafine fibers and a polymeric elastomer, has superior characteristics compared to natural leather, such as high durability and uniformity of quality. Therefore, it is used in various fields such as clothing materials, vehicle interior materials, interior goods, shoes, and clothing. In particular, it is often used as a clothing material because it is easier to care for (easy care property) compared to natural leather, it can be given functionality such as stretchability, and it has a soft texture, and methods for obtaining artificial leather suitable for use in clothing have been proposed (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-261082 A [Patent Document 2] International Publication No. 2017 / 033702 Summary of the Invention [Problem to be solved by the invention]
[0004] In the technology disclosed in Patent Document 1, the artificial leather has elasticity, and it is possible to obtain artificial leather suitable for use in jackets and the like. In addition, in the technology disclosed in Patent Document 2, it is possible to obtain clothing having artificial leather with excellent wiping performance on the sleeves. When artificial leather is used as clothing, from the viewpoint of easy care, if dirt adheres to the artificial leather, the dirt can be removed by dry cleaning or the like. However, when general artificial leather is washed in a washing machine for the purpose of more convenient dirt removal, the fibers fall off due to friction and rubbing, and the deterioration of the polymeric elastomer is accelerated, so that the appearance and physical properties are significantly deteriorated, and it is still difficult to care for compared to other clothing materials.
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an artificial leather which comprises a fiber-entangled body in which a woven fabric is entangled and integrated with a nonwoven fabric made of ultrafine fibers, and a polymeric elastomer, which is less susceptible to fiber shedding due to friction or rubbing, and which is less susceptible to deterioration in appearance and physical properties, particularly even when washed in a washing machine. [Means for solving the problem]
[0006] As a result of extensive research by the present inventors to achieve the above object, it was found that in an artificial leather containing a woven fabric as a constituent component, the ultrafine fibers on the surface of the artificial leather closer to the woven fabric are weakly entangled with each other compared to the ultrafine fibers on the surface farther from the woven fabric, and more fibers fall off when friction or kneading is applied. In addition, it was found that in the case where the surface closer to the woven fabric has nap made of ultrafine fibers, in particular, if the nap length is too long or the variation in the nap length is too large, more fibers fall off when friction or kneading is applied.
[0007] The present invention has been completed based on these findings, and provides the following inventions.
[0008] That is, the artificial leather of the present invention is an artificial leather comprising a fiber-entangled body formed by entangling a woven fabric with a nonwoven fabric made of ultrafine fibers having an average single fiber diameter of 1 μm or more and 10 μm or less, and a polymer elastomer, and satisfies the following requirements (1) to (3). (1) The above-mentioned artificial leather The surface close to the fabric and the surface opposite to the surface close to the fabric Both surfaces are napped surfaces. In the fiber entanglement, the woven fabric is not exposed on the surface of the fiber entanglement. (2) Of the surface having nap, the side closest to the fabric Face The average standing length is 50 μm or more and 150 μm or less, and the CV value of the standing length is 30% or less. (3) In the cross section in the thickness direction of the artificial leather, the following formula (i) is satisfied: B>A / 2 (i) Here, A is the thickness of the fabric (μm), B is the thickness of the fabric and the side close to the fabric. Face is the distance (μm) between
[0009] In a preferred embodiment of the artificial leather of the present invention, the polymeric elastomer is a polycarbonate polyurethane.
[0010] According to a preferred embodiment of the artificial leather of the present invention, the nonwoven fabric is made of a polyester-based resin, and the polyester-based resin contains a component derived from 1,2-propanediol in an amount of 1 ppm or more and 500 ppm or less.
[0011] According to a preferred embodiment of the artificial leather of the present invention, the biomass plastic content as defined by ISO16620 (2015) is 10% or more and 100% or less. Effect of the Invention
[0012] The artificial leather of the present invention can be obtained in which fiber loss due to friction or rubbing is minimal, and in particular, deterioration in appearance and physical properties is minimal even when washed in a washing machine. Furthermore, the artificial leather of the present invention has an elegant appearance and soft feel similar to natural leather, and can be used in a wide range of applications, from furniture, chairs, and vehicle interior materials to clothing, but is particularly suitable for clothing applications from the viewpoint of ease of care. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The artificial leather of the present invention is an artificial leather comprising a fiber-entangled body obtained by entangling a woven fabric with a nonwoven fabric made of ultrafine fibers having an average single fiber diameter of 1 μm or more and 10 μm or less, and a polymeric elastomer, and satisfies the following requirements (1) to (3). (1) The artificial leather The surface close to the fabric and the surface opposite to the surface close to the fabric Both surfaces are napped surfaces. In the fiber entanglement, the woven fabric is not exposed on the surface of the fiber entanglement. (2) The side of the napped surface that is closer to the fabric Face The average standing length is 50 μm or more and 150 μm or less, and the CV value of the standing length is 30% or less. (3) In the cross section in the thickness direction of the artificial leather, the following formula (i) is satisfied: B>A / 2 (i) Here, A is the thickness of the fabric (μm), and B is the thickness of the fabric and the side close to the fabric. Face The components are described in detail below, but the present invention is not limited to the scope of the following description as long as it does not deviate from the gist of the present invention.
[0014] [Nonwoven fabric] The nonwoven fabric for the artificial leather of the present invention is made of ultrafine fibers having an average single fiber diameter of 1 μm to 10 μm. As a component constituting the ultrafine fibers, polyester-based resins and polyamide-based resins are preferably used from the viewpoint of durability, particularly mechanical strength, and the like, and polyester-based resins having excellent heat resistance are more preferably used.
[0015] Examples of the polyester resin include polyethylene terephthalate, polytrimethylene terephthalate, polytetramethylene terephthalate, polycyclohexylene dimethylene terephthalate, polyethylene-2,6-naphthalenedicarboxylate, and polyethylene-1,2-bis(2-chlorophenoxy)ethane-4,4'-dicarboxylate. Among them, polyethylene terephthalate, which is the most widely used, or a polyester copolymer mainly containing ethylene terephthalate units is preferably used.
[0016] When a polyester-based resin is used as a component constituting the ultrafine fibers, it is preferable that the polyester constituting the polyester-based resin contains a component derived from 1,2-propanediol in an amount of 1 ppm or more and 500 ppm or less in order to improve the heat resistance and abrasion resistance during thermoforming of the artificial leather.
[0017] The component derived from 1,2-propanediol here is determined by the total amount of 1,2-propanediol detected when polyester is decomposed and analyzed by the method described in the Examples section, and is considered to be the total amount of 1,2-propanediol derived from 1,2-propanediol copolymerized in the polymer chain and 1,2-propanediol mixed between polymers. In other words, this 1,2-propanediol may be partially copolymerized in the polyester main chain, or it may be contained as a single substance without being copolymerized. When polymers other than polyester are contained in the fiber, the polyester is selectively extracted using a solvent such as 1,1,1,3,3,3-hexafluoro-2-propanol or orthochlorophenol, and the concentration is determined by the method described in the Examples section after distilling off the solvent.
[0018] Inorganic particles such as titanium oxide, lubricants, heat stabilizers, ultraviolet absorbers, conductive agents, heat storage agents, antibacterial agents, and the like can be added to the components constituting the ultrafine fibers according to various purposes, within the scope of not impairing the object of the present invention.
[0019] From the viewpoint of processing operability, the cross-sectional shape of the ultrafine fibers is preferably a round cross-section, but cross-sectional shapes of irregular cross-sections such as an ellipse, a polygon such as a flattened or triangular shape, a sector shape, a cross shape, a hollow shape, a Y shape, a T shape, or a U shape can also be used.
[0020] The average single fiber diameter of the ultrafine fibers according to the present invention is 1 μm or more and 10 μm or less. By making the average single fiber diameter of the ultrafine fibers 1.0 μm or more, preferably 1.5 μm or more, more preferably 2.0 μm or more, excellent effects are obtained in color development after dyeing, light fastness and friction fastness, and stability during spinning. On the other hand, by making it 10.0 μm or less, preferably 6.0 μm or less, more preferably 5.0 μm or less, an artificial leather with excellent surface quality that is dense and soft to the touch can be obtained.
[0021] In the present invention, the average single fiber diameter of ultrafine fibers is calculated by taking a scanning electron microscope (SEM) photograph of the cross section of the artificial leather, randomly selecting 10 ultrafine fibers that are circular or elliptical and close to circular, measuring the single fiber diameter (μm), calculating the arithmetic average value of the 10 fibers, and rounding off to the nearest tenth. However, when ultrafine fibers with a modified cross section are used, the cross-sectional area (μm 2 ) is measured, and the diameter when the cross section is regarded as a circle, i.e., the circle equivalent diameter, is calculated to obtain the diameter of the single fiber (μm).
[0022] Furthermore, the artificial leather of the present invention has the nonwoven fabric made of the ultrafine fibers as a constituent element, i.e., the aggregate of ultrafine fibers in the artificial leather is in the form of a nonwoven fabric. By forming the nonwoven fabric, it is possible to obtain an artificial leather having a uniform and elegant appearance when the surface is raised, as well as a soft texture.
[0023] As the form of the nonwoven fabric, either a long fiber nonwoven fabric such as a spunbonded nonwoven fabric or a meltblown nonwoven fabric, or a short fiber nonwoven fabric composed of fibers of a certain length can be used. However, a short fiber nonwoven fabric is preferred because it has a large number of raised fibers on the product surface and is likely to give an elegant appearance.
[0024] The fiber length of the ultrafine fibers when used in the short fiber nonwoven fabric is preferably 25 to 90 mm. By making the fiber length 90 mm or less, more preferably 80 mm or less, and even more preferably 70 mm or less, the artificial leather obtained has good quality and texture. On the other hand, by making the fiber length 25 mm or more, more preferably 35 mm or more, and even more preferably 40 mm or more, the artificial leather has excellent abrasion resistance.
[0025] [fabric] As the type of fiber constituting the woven fabric of the artificial leather of the present invention, it is preferable to use filament yarn, spun yarn, a mixed composite yarn of filament yarn and spun yarn, etc., and from the standpoint of durability, particularly mechanical strength, it is more preferable to use a multifilament made of a polyester-based resin or a polyamide-based resin.
[0026] The average single fiber diameter of the fibers constituting the woven fabric is preferably 1 μm or more and 50 μm or less. By making the average single fiber diameter of the fibers constituting the woven fabric 50.0 μm or less, more preferably 15.0 μm or less, and even more preferably 13.0 μm or less, an artificial leather with excellent flexibility can be obtained. On the other hand, by making the average single fiber diameter 1.0 μm or more, more preferably 8.0 μm or more, and even more preferably 9.0 μm or more, the shape stability of the product as an artificial leather can be improved.
[0027] In the present invention, the average single fiber diameter of the fibers constituting the woven fabric is calculated by taking a scanning electron microscope (SEM) photograph of the cross section of the artificial leather, randomly selecting 10 fibers constituting the woven fabric, measuring the single fiber diameters of the fibers, calculating the arithmetic average of the 10 fibers, and rounding off to the nearest tenth. However, when a fiber with a modified cross section is used, the cross-sectional area (μm 2 ) is measured, and the diameter when the cross section is considered to be a circle, i.e., the equivalent circle diameter, is calculated to determine the fiber diameter (μm).
[0028] When the fibers constituting the woven fabric are multifilament, the total fineness of the multifilament is preferably 30 dtex or more and 170 dtex or less, as measured by "8.3.1 Correct fineness b) Method B (simplified method)" of "8.3 Fineness" of JIS L1013:2010 "Testing methods for chemical fiber filament yarns."
[0029] By setting the total fineness of the multifilaments constituting the woven fabric to 170 dtex or less, more preferably 150 dtex or less, an artificial leather with excellent flexibility can be obtained. On the other hand, by setting the total fineness to 30 dtex or more, not only the shape stability of the product as an artificial leather is improved, but also the fibers constituting the woven fabric are less likely to be exposed on the surface of the artificial leather when the nonwoven fabric and the woven fabric are entangled and integrated by needle punching or the like, which is preferable. In this case, the total fineness of the multifilaments of the warp and weft threads may be the same or different.
[0030] Furthermore, in the case of the multifilament constituting the woven fabric, the twist number is preferably 1000 to 4000 T / m. By setting the twist number to 4000 T / m or less, more preferably 3500 T / m or less, and even more preferably 3000 T / m or less, an artificial leather having excellent flexibility can be obtained, and by setting the twist number to 1000 T / m or more, more preferably 1500 T / m or more, and even more preferably 2000 T / m or more, damage to the fibers constituting the woven fabric can be prevented when the nonwoven fabric and the woven fabric are entangled and integrated by needle punching or the like, and the mechanical strength of the artificial leather can be excellent, which is preferable.
[0031] The basic weave of the fabric may be twill or satin, but a plain weave, which is less prone to misalignment, is preferably used.
[0032] The weave density of the woven fabric is preferably adjusted so that both the warp and weft threads in the artificial leather are 40 threads / 2.54 cm to 200 threads / 2.54 cm. By setting the weave density of the woven fabric constituting the artificial leather to 40 threads / 2.54 cm or more, more preferably 60 threads / 2.54 cm or less, an artificial leather with excellent shape stability can be obtained. On the other hand, by setting the weave density of the woven fabric constituting the artificial leather to 200 threads / 2.54 cm or less, more preferably 150 threads / 2.54 cm or less, not only can the texture of the artificial leather be made soft, but also the entanglement of the fibers of the nonwoven fabric is not hindered when the nonwoven fabric and the woven fabric are entangled and integrated, and as a result, fiber shedding of the artificial leather can be suppressed.
[0033] [Polymer elastomer] The polymeric elastomer constituting the artificial leather of the present invention plays the role of a binder that holds the ultrafine fibers in the artificial leather. Therefore, in order to give the artificial leather a softer texture, it is preferable to use polyurethane, polyurethane, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), acrylic resin, etc. as the polymeric elastomer. Among them, it is more preferable to use polyurethane as the main component. By using polyurethane, it is possible to obtain artificial leather that has a rich touch, a leather-like appearance, and physical properties that can withstand practical use. In addition, in the present invention, "main component" means that the mass of polyurethane is more than 50% by mass of the total mass of the polymeric elastomer.
[0034] In the present invention, when polyurethane is used, it is possible to use either an organic solvent-based polyurethane that is dissolved in an organic solvent, or a water-dispersed polyurethane that is dispersed in water. As the polyurethane, a polyurethane obtained by reacting a polymer diol, an organic diisocyanate, and a chain extender is preferably used.
[0035] When a polyurethane is used in the present invention, the polymer diol used may be at least one selected from polymer diols such as polyester diols, polyether diols, polycarbonate diols, and polyester polyether diols having an average molecular weight of 500 or more and 3,000 or less. It is preferable that the polyurethane contains a polycarbonate diol that is resistant to loss of its function as a binder after repeated washing and has excellent hydrolysis resistance.
[0036] In addition, the polymer elastomer may contain various additives depending on the purpose, for example, pigments such as carbon black, flame retardants such as "phosphorus-based, halogen-based, and inorganic" antioxidants such as "phenol-based, sulfur-based, and phosphorus-based" antioxidants, ultraviolet absorbers such as "benzotriazole-based, benzophenone-based, salicylate-based, cyanoacrylate-based, and oxalic acid anilide-based" light stabilizers such as "hindered amine-based and benzoate-based" stabilizers against hydrolysis such as polycarbodiimide, plasticizers, antistatic agents, surfactants, coagulation adjusters, and dyes.
[0037] In general, the content of the polymer elastomer in the artificial leather can be appropriately adjusted taking into consideration the type of polymer elastomer used, the manufacturing method of the polymer elastomer, and the texture and physical properties, but in the present invention, the content of the polymer elastomer is preferably 20% by mass or more and 50% by mass or less relative to the mass of the nonwoven fabric. By making the content of the polymer elastomer 20% by mass or more, more preferably 25% by mass or more, the abrasion resistance of the artificial leather can be improved. On the other hand, by making the content of the polymer elastomer 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, the artificial leather can be made more flexible.
[0038] [Artificial leather] The artificial leather of the present invention comprises the above-mentioned fiber entanglement body and a polymeric elastomer. The surface close to the fabric and the surface opposite to the surface close to the fabric Both surfaces have nap. In the fiber entanglement, the woven fabric is not exposed on the surface of the fiber entanglement.First, the side of the surface with the nap closest to the fabric Face In the present invention, the term "surface having nap" refers to a surface having a napped layer of ultrafine fibers having such length and directional flexibility that a so-called finger mark appears when the surface is traced with a finger, and the side closer to the woven fabric refers to the side closest to the napped surface from the center of the woven fabric, which is the midpoint between the highest point and the lowest point in the thickness direction of the woven fabric, when a cross-sectional photograph of the artificial leather is taken.
[0039] Side closest to fabric Face The average nap length is 50 μm or more and 150 μm or less. By having the average nap length of 50 μm or more, preferably 60 μm or more, and more preferably 80 μm or more, the side closer to the woven fabric can be easily obtained. Face By making the average nap length 150 μm or less, preferably 130 μm or less, and more preferably 120 μm or less, it is possible to prevent the napped ultrafine fibers from becoming entangled when the artificial leather is rubbed, and thus prevent the fibers from becoming clumpy and falling off when the artificial leather is rubbed.
[0040] Also, the side closest to the fabric Face The CV value (Coefficient of Variation) of the nap length is 30% or less. By making the CV value of the nap length 30% or less, preferably 25% or less, more preferably 20% or less, it is possible to prevent the long fibers from being entangled due to the mixture of fibers with long and short nap lengths, resulting in the ultrafine fibers falling off. The lower limit of the CV value of the nap length is not particularly limited, but is preferably 5% or more from the viewpoints of process stability and productivity.
[0041] Next, the side closest to the fabric Face The opposite side of the fabric is explained. FaceThe nap on the opposite side is preferably 100 μm or more, more preferably 150 μm or more, and even more preferably 200 μm or more in order to obtain an elegant appearance, while the average nap length is preferably 400 μm or less, and more preferably 350 μm or less in order to suppress fiber shedding during friction.
[0042] In the present invention, the average nap length and the CV value of the nap length are calculated by photographing a cross section of the artificial leather at a magnification of 50 times using a scanning electron microscope (SEM) while the nap of the artificial leather is inverted using a lint brush or the like, measuring the height of the nap portion (a layer consisting only of ultrafine fibers) at 10 points, and calculating the average value and CV value.
[0043] Furthermore, the artificial leather of the present invention satisfies the following formula (i) in a cross section in the thickness direction of the artificial leather: B>A / 2 (i) Here, A is the thickness of the fabric (μm), and B is the thickness of the fabric and the side close to the fabric. Face and B. A and B satisfying formula (i) means that the layer of nonwoven fabric covering the woven fabric is thin, and the layer of the woven fabric is less likely to be damaged when forming the nap on the surface closer to the woven fabric during production, making it possible to obtain an artificial leather with high mechanical strength. Furthermore, even in the unlikely event that fibers on the surface fall off, the woven fabric is less likely to be exposed on the surface, making it possible to obtain an artificial leather whose appearance quality is not impaired even with long-term use.
[0044] The above formula (i) preferably satisfies the following formula (i').
[0045] A>B (i') In the present invention, the thickness A (μm) of the woven fabric is measured by photographing the cross section of the artificial leather with a scanning electron microscope (SEM, for example, "VE-7800" manufactured by Keyence Corporation) at a magnification of 50 to 200 times, measuring the height of the woven fabric at 10 points, and calculating the average value. Face The distance B (μm) between the fabric and the side close to the fabric was also calculated using the image used to calculate A. FaceThe distance to the tip (including the nap-standing portion) is measured at 10 points and the average value is calculated.
[0046] The artificial leather of the present invention preferably has a thickness of 0.2 mm or more and 1.0 mm or less, as measured by "6.1.1 A method" of "6.1 Thickness (ISO method)" of JIS L1913:2010 "General nonwoven fabric test methods". By making the thickness of the artificial leather 0.2 mm or more, more preferably 0.3 mm or more, and even more preferably 0.4 mm or more, it is possible to obtain an artificial leather that is excellent in processability during production as well as a rich and excellent texture. On the other hand, by making the thickness 1.0 mm or less, more preferably 0.9 mm or less, and even more preferably 0.8 mm or less, it is possible to obtain an artificial leather that is excellent in moldability and flexible.
[0047] Furthermore, from the viewpoint of carbon neutrality, the artificial leather of the present invention preferably has a biomass plastic content of 10% or more as defined by ISO16620 (2015). From the viewpoint of reducing the environmental load, the biomass plastic content is more preferably 15% or more, and even more preferably 20% or more.
[0048] In addition, the artificial leather of the present invention is a leather that has been washed in accordance with the ISO 6330 (2012) C4N method. When a washing test is performed on one piece of the artificial leather, and the fiber waste attached to a collection bag attached to a drainage hose after the test is collected using a membrane filter, the amount of fiber waste is 10.0 (mg / 100 cm of artificial leather). 2 ) or less. Among them, it is preferable that the surface roughness is 8.0 (mg / 100 cm of artificial leather) or less. 2 ) or less, more preferably 6.0 (mg / 100 cm of artificial leather 2 ) or less, more preferably 5.0 (mg / 100 cm of artificial leather 2 ) or less, the artificial leather loses less fibers during washing and has a smaller environmental impact.
[0049] In the present invention, when a washing test is conducted according to the ISO6330 (2012) C4N method on one piece of the artificial leather, and the amount of fiber debris adhered to a collection bag attached to a drain hose after the test is collected using a membrane filter, the amount of fiber debris refers to a value measured and calculated according to the following procedure. (1) Test piece 100cm from artificial leather 2 is collected. (2) Without putting any laundry or detergent into the washing machine, wash the laundry and clean the washing machine in accordance with the ISO 6330 (2012) C4N method. (3) With a collection bag made from a 10μm mesh "nylon screen" ("NY10-HC" by Fluoro Industries Co., Ltd.) attached to the drain hose of the washing machine, one test piece to be evaluated is placed in the washing machine and washed according to the ISO6330 (2012) C4N method. However, detergent and load cloth are not used. (4) After washing, the fiber debris adhering to the “nylon screen” is suction filtered using a polycarbonate membrane (“K040A047A” (manufactured by Advantec Toyo Co., Ltd.)) whose mass has been measured in advance. (5) The polycarbonate membrane and fiber debris after filtration are dried at 105°C for 1 hour, the mass of the residue is measured, and the difference from the mass before filtration is the amount of fiber debris after washing.
[0050] In addition, in an abrasion resistance test of the artificial leather of the present invention measured by "8.19.5 E method (Martindale method)" of "8.19 Abrasion resistance and discoloration due to friction" of JIS L1096:2010 "Testing methods for woven and knitted fabrics", the weight loss of the artificial leather after abrasion 20,000 times at a pressing load of 12.0 kPa is preferably 10 mg or less, more preferably 8 mg or less, and even more preferably 6 mg or less on both sides of the artificial leather. By having the weight loss of the artificial leather on both sides of 10 mg or less, it is possible to prevent contamination due to fluff shedding during actual use and fiber shedding during washing.
[0051] [Manufacturing method of artificial leather] The method for producing an artificial leather of the present invention is a method for producing an artificial leather comprising a fiber-entangled body obtained by entangling a woven fabric with a nonwoven fabric made of ultrafine fibers having an average single fiber diameter of 1 μm to 10 μm, and a polymeric elastomer, and forming naps on both surfaces of the artificial leather, the side closest to the woven fabric being Face The average nap length of the above-mentioned fibers is set to 50 μm or more and 150 μm or less, and the CV value of the nap texture is set to 30% or less, thereby producing the above-mentioned artificial leather. The method for producing the artificial leather of the present invention will be described in further detail below.
[0052] The fiber-entangled body used in the method for producing an artificial leather of the present invention is obtained by entangling and integrating a woven fabric with a nonwoven fabric made of ultrafine fibers having an average single fiber diameter of 1 μm to 10 μm. As the fibers constituting the nonwoven fabric before being entangled and integrated with the woven fabric, ultrafine fibers having an average single fiber diameter of 1 μm to 10 μm or ultrafine fiber-developing fibers capable of developing ultrafine fibers having an average single fiber diameter of 1.0 μm to 10.0 μm by being converted into ultrafine fibers in a later process may be used, but it is preferable to use ultrafine fiber-developing fibers, which can prevent damage to the ultrafine fibers when nonwoven fabrics are entangled with each other or when a nonwoven fabric is entangled with a woven fabric.
[0053] When an ultrafine fiber-forming fiber is used, it is possible to employ islands-in-sea composite fibers in which two thermoplastic resin components having different solvent solubilities are used as a sea component and an island component, and the sea component is dissolved and removed using a solvent or the like to convert the island components into ultrafine fibers; or peel-type composite fibers in which two thermoplastic resin components are alternately arranged in a radial or multi-layered fiber cross section, and each component is peeled and divided to split into ultrafine fibers.
[0054] Among these, islands-in-sea type composite fibers are preferably used from the viewpoints of texture and surface quality of artificial leather, since appropriate gaps can be provided between island components, i.e., between ultrafine fibers inside a fiber bundle, by removing the sea component.
[0055] For islands-in-sea type composite fibers, a method using a polymer mutual alignment body in which two components, a sea component and an island component, are mutually aligned and spun using an islands-in-sea type composite spinneret, or a mixed spinning method in which two components, a sea component and an island component, are mixed and spun, can be used. From the viewpoint of obtaining ultrafine fibers with uniform single fiber fineness, the islands-in-sea type composite fibers using the method using a polymer mutual alignment body are preferably used.
[0056] The sea component of the islands-in-sea type composite fiber can be made of polyethylene, polypropylene, polystyrene, copolymer polyesters obtained by copolymerizing sodium sulfoisophthalic acid, polyethylene glycol, etc., and polylactic acid, etc. Among these, polystyrene and copolymer polyesters are preferably used from the viewpoints of spinnability, ease of elution, etc.
[0057] When the above islands-in-sea type composite fiber is used, it is preferable to use an islands-in-sea type composite fiber in which the strength of the island component fibers is 0.3 cN or more. When the strength of the island component fibers is 0.3 cN or more, more preferably 0.35 cN or more, and further preferably 0.4 cN or more, the abrasion resistance of the artificial leather can be improved.
[0058] In the present invention, the strength of the island component fibers of the islands-in-sea type composite fiber is calculated by the following method. (1) Ten islands-in-the-sea composite fibers, each 20 cm long, are bundled together. (2) After dissolving and removing the sea component from the sample (1), air-dry it. (3) In accordance with JIS L1013:2010 "Test methods for chemical fiber filament yarn", "8.5 Tensile strength and elongation", "8.5.1 Standard time test", the test shall be carried out 10 times under the conditions of a grip length of 5 cm, a pulling speed of 5 cm / min, and a load of 2 N (N=10). (4) The arithmetic mean value (cN) of the test results obtained in (3) above, rounded off to two decimal places, shall be the strength of the island component fibers of the islands-in-sea type composite fiber.
[0059] Next, the obtained ultrafine fiber-developing fibers are made into a fiber web by a cross wrapper or the like, and entangled to obtain a nonwoven fabric. As a method for entangling the fiber web to obtain a nonwoven fabric, needle punching, water jet punching, etc. can be used.
[0060] As for the form of the nonwoven fabric, either a short fiber nonwoven fabric or a long fiber nonwoven fabric can be used as described above. However, a short fiber nonwoven fabric is preferred because it has more ultrafine fibers oriented in the thickness direction of the artificial leather than a long fiber nonwoven fabric, and therefore it is possible to obtain a highly dense feel on the surface of the artificial leather when it is raised.
[0061] When the resulting ultrafine fiber-developing fibers are to be used for forming a short fiber nonwoven fabric, the fibers are preferably subjected to a crimping process and cut to a predetermined length before being formed into a nonwoven fabric. In this case, the crimping process and the cutting process can be carried out by known methods.
[0062] To integrate a woven fabric into a nonwoven fabric, a woven fabric can be laminated on one or both sides of the nonwoven fabric, or a woven fabric can be sandwiched between multiple nonwoven fabric webs and then the fibers of the nonwoven fabric and the woven fabric can be entangled by needle punching, water jet punching, or the like.
[0063] When needle punching is used, the barb direction of the needle punch is preferably perpendicular to the traveling direction of the nonwoven fabric and woven fabric at 90±25°, thereby making it less likely to catch the weft yarn of the woven fabric, which is easily damaged.
[0064] In addition, when a water jet punching process is used, the water in the water jet punching process is preferably in the form of a columnar flow. Specifically, in a preferred embodiment, water is ejected from a nozzle having a diameter of 0.05 to 1.0 mm at a pressure of 1 to 60 MPa.
[0065] The apparent density of the fiber entanglement after needle punching or water jet punching is 0.15 g / cm 3 More than 0.45g / cm 3The apparent density is preferably 0.15 g / cm or less. 3 By adjusting the apparent density to 0.45 g / cm or more, an artificial leather having excellent shape stability and dimensional stability can be obtained. 3 By setting the above, it is possible to form a sufficient space for providing the polymeric elastomer.
[0066] When a woven fabric is laminated on one or both sides of a nonwoven fabric, it is preferable to entangle and integrate the woven fabric so that the woven fabric is completely covered with the fibers constituting the nonwoven fabric. More specifically, in a fiber-entangled body in which the woven fabric is entangled and integrated with the nonwoven fabric, it is preferable that the woven fabric is not exposed on the surface of the fiber-entangled body.
[0067] It is also a preferred embodiment that the fiber entanglement is subjected to a heat shrinkage treatment with hot water or steam in order to improve the denseness of the fibers.
[0068] Furthermore, the water-soluble resin can be added by impregnating the fiber-entangled body with an aqueous solution of the water-soluble resin and drying it. By adding the water-soluble resin to the fiber-entangled body, the fibers are fixed and the dimensional stability is improved. The water-soluble resin referred to here is a resin that has a hydrophilic group and has the property of forming a viscous liquid when dissolved in water, and specific examples of the water-soluble resin include polyvinyl alcohol (hereinafter sometimes abbreviated as PVA) and polyvinylpyrrolidone (hereinafter sometimes abbreviated as PVP).
[0069] When ultrafine fiber-developing fibers are used as the fibers constituting the nonwoven fabric, the obtained fiber-entanglement body is treated with a solvent to develop ultrafine fibers having an average single fiber diameter of 1 μm or more and 10 μm or less from the ultrafine fiber-developing fibers. The development of ultrafine fibers can also be carried out after the application of the polymeric elastomer described below.
[0070] When the ultrafine fiber-producing fiber is an islands-in-the-sea type composite fiber, the solvent for dissolving and removing the sea component can be an organic solvent such as toluene or trichloroethylene when the sea component is polyethylene, polypropylene, or polystyrene. Also, when the sea component is a copolymer polyester or polylactic acid, an alkaline aqueous solution such as sodium hydroxide can be used. Also, when the sea component is a water-soluble thermoplastic polyvinyl alcohol resin, hot water can be used.
[0071] The fiber-entangled body obtained by entangling and integrating the woven fabric with the nonwoven fabric is then impregnated with a polymer elastomer solution and solidified to provide the polymer elastomer. In this case, the polymer elastomer can be fixed to the nonwoven fabric by a wet coagulation method in which the fiber-entangled body is impregnated with a polymer elastomer solution and then immersed in a coagulation liquid such as water to coagulate the fiber-entangled body, or a dry coagulation method in which the solvent in the polymer elastomer solution is removed by heating to coagulate the fiber-entangled body. These methods can be appropriately selected depending on the type of polymer elastomer used.
[0072] As a solvent used when providing polyurethane as a polymeric elastomer, N,N'-dimethylformamide, dimethylsulfoxide, etc. are preferably used. In addition, a water-dispersed polyurethane liquid in which polyurethane is dispersed in water as an emulsion may be used.
[0073] When a fiber-entangled body in which woven fabrics are laminated on both sides of a nonwoven fabric is used, it is a preferred embodiment to cut the obtained sheet in half in the thickness direction.
[0074] Furthermore, the sheet-like material (including a cut product of the sheet) made of the fiber-entangled body and the polymeric elastomer is subjected to a nap raising treatment to form raised naps, thereby obtaining an artificial leather. The nap raising treatment can be performed by a method such as grinding with sandpaper. It is also a preferred embodiment to add a lubricant such as a silicone emulsion or an antistatic agent before the nap raising treatment.
[0075] When using sandpaper to perform the nap treatment, Later Side closest to fabric The surface that is the surface ofIn the raising treatment of step 2, it is preferable to adjust the nap length within a predetermined range and to prevent damage to the woven fabric by adjusting the coarseness of the sandpaper, the grinding resistance, etc.
[0076] Furthermore, the above artificial leather has at least , later The side closest to the fabric The surface that is the surface of It is preferable to perform a shearing process on the fabric. By performing the shearing process, Later Surface closest to the fabric The surface that becomes The nap length can be made more uniform, and the CV value of the nap length of the resulting artificial leather can be easily made 30% or less.
[0077] The above artificial leather can be dyed as required. Examples of the dyeing process include a flow dyeing process using a jigger dyeing machine or a flow dyeing machine, a dip dyeing process such as a thermosol dyeing process using a continuous dyeing machine, or a printing process on the napped surface using roller printing, screen printing, inkjet printing, sublimation printing, vacuum sublimation printing, etc. Among these, it is preferable to use a flow dyeing machine from the viewpoint of quality and grade, since a soft texture can be obtained. In addition, various resin finishing processes can be performed after dyeing as required.
[0078] Furthermore, the surface of the above-mentioned artificial leather can be given a design, if necessary, for example, post-processing such as perforation, embossing, laser processing, pinsonic processing, and printing. EXAMPLES
[0079] Next, the artificial leather of the present invention will be described in more detail using examples, but the present invention is not limited to these examples. Next, the evaluation methods and measurement conditions used in the examples will be described. However, in the measurement of each physical property, unless otherwise specified, the measurement was performed based on the above-mentioned method.
[0080] [Measurement method and evaluation processing method] (1) Amount of fiber waste during washing Artificial leather 10cm x 10cm (100cm 2 A test piece of 100 mm was cut out and subjected to the washing test by the above method, and the amount of fiber waste was calculated. The measurement was performed twice, and the average value was regarded as the amount of fiber waste after washing.
[0081] (2) Mass loss during abrasion testing The abrasion resistance test was carried out using a James H. Heal & Co. "Model 406" abrasion tester and the same company's "Abrastive Cloth SM25" as the standard friction cloth. Measurements were carried out twice for each side of the artificial leather, and the average value was taken as the mass loss during the abrasion test.
[0082] (3) Appearance after abrasion test After carrying out the above (2) test, the side of the artificial leather closest to the fabric Face The result was visually inspected, and samples in which the woven fabric was not exposed on the surface were rated as passed (◯), and samples in which the woven fabric was exposed on the surface were rated as failed (×).
[0083] (4) Content of components derived from 1,2-propanediol in polyester: First, a 1000 μg / ml aqueous solution of 1,2-butanediol was prepared, and this was used as internal standard solution A. 0.1 g of sample was weighed into a vial, to which 0.015 ml of internal standard solution A and 1 ml of ammonia water were added, and the vial was sealed and heated at a temperature of 150° C. for 3 hours, and then allowed to cool to room temperature (25° C.). Next, 2 ml of methanol and 2.0 g of terephthalic acid were added, followed by shaking for 15 minutes and centrifuging at 4000 G for 3 minutes. The supernatant was removed and measured using a gas chromatograph (Hewlett Packard 5890 series II, injection port: split / splitless injection port, detector: hydrogen flame ionization detector) under the following set conditions, and the content was determined using the calibration curve described below. Injector temperature: 220℃ Column head pressure: 20psi Carrier gas: Helium Sample introduction method: Split (linear flow rate 25 ml / min) ·Bulkhead purge: Helium 3.0ml / min Sample volume: 1.0 μl Detector temperature: 220℃ Gas flow rate: Hydrogen 40ml / min, Air 400ml / min, Nitrogen 40ml / min Oven heating start temperature: 60℃ (holding time 2 minutes) Oven temperature rise stop temperature: 220℃ (holding time 2 minutes) Oven heating rate: 20°C / min (linear ramp).
[0084] The calibration curve of 1,2-propanediol was prepared by the following procedure. A 1000 μg / ml aqueous solution of 1,2-propanediol was prepared as standard mother solution B, and then 0.003 to 0.08 ml of standard mother solution B and 0.025 ml of internal standard solution A were added to a 5 ml measuring flask, and the volume was adjusted to a constant volume with a mixed solvent (methanol:purified water = 2:1, containing 1.1% ethylene glycol). Seven types of standard solution C were prepared by varying the amount of standard mother solution B. The amount of standard mother solution B added was selected so that the concentration of 1,2-propanediol was sufficient for the measurement of the sample. The prepared standard solutions C were each measured by gas chromatography under the above-mentioned conditions, and the peak area ratio of 1,2-propanediol to the internal standard and the concentration ratio of 1,2-propanediol to the internal standard in standard solution C were plotted on a graph to prepare a calibration curve of 1,2-propanediol.
[0085] (5) Thickness of the fabric (A) and the fabric and the side close to the fabric Face Distance between (B) The cross section of the artificial leather was observed at a magnification of 100 times using a scanning electron microscope (SEM, Keyence Corporation "VE-7800"), and the thickness of the fabric (A) and the thickness of the fabric and the area close to the fabric were measured using the above method. Face The distance (B) between the two points was calculated. The measurement was performed three times, and the average value was calculated. The thickness of the fabric (A) and the distance between the fabric and the surface having the nap that is closer to the fabric (B) It was decided.
[0086] [Example 1] <Step of producing fiber entanglement> The island component was polyethylene terephthalate (PET A) with an intrinsic viscosity (IV value) of 0.73, a biomass resource-derived ethylene glycol polymerization component, and 15 ppm of 1,2-propanediol-derived component, and the sea component was polystyrene with an MFR of 65. The fibers were melt spun using an islands-in-sea composite spinneret with 16 islands / hole under the conditions of a spinning temperature of 285°C, an islands / sea mass ratio of 80 / 20, a throughput of 1.2 g / min / hole, and a spinning speed of 1100 m / min. The fibers were then stretched 2.7 times in a spinning oil bath at 90°C, crimped using a push-in crimper, and cut to a length of 51 mm to obtain raw fibers for islands-in-sea composite fibers.
[0087] Next, the raw cotton of the islands-in-the-sea type composite fiber was used to form a laminated web through carding and cross-wrapping processes, and further, a plain weave fabric (weight 75 g / m) with a warp density of 95 threads / 2.54 cm and weft density of 76 threads / 2.54 cm was produced using a multifilament (average single fiber diameter: 11 μm, total fineness: 84 dtex) made of polyethylene terephthalate with an intrinsic viscosity (IV value) of 0.65 and a polymerization component of ethylene glycol derived from biomass resources, twisted at 2500 T / m for both the weft and warp. 2 ) was laminated on the top and bottom of the laminated web, and the density was 2500 threads / cm 2 The fabric is needle punched with the number of punches, and the weight is 700g / m 2 Thus, a fiber-entangled body having a thickness of 3.0 mm was obtained.
[0088] The fiber-entangled body obtained as described above was shrunk with hot water at a temperature of 96°C, and then impregnated with a 5% by mass aqueous solution of PVA having a degree of saponification of 88%. The fiber-entangled body was then squeezed with a roll and dried with hot air at a temperature of 120°C for 10 minutes while allowing the PVA to migrate, thereby obtaining a sheet with PVA having a PVA mass of 7.5% by mass relative to the mass of the fiber-entangled body.
[0089] The sheet with PVA obtained as described above was immersed in trichloroethylene, and squeezed with a mangle and compressed 10 times to dissolve and remove the sea component and compress the sheet with PVA, thereby obtaining a sea-free PVA sheet consisting of an ultrafine fiber nonwoven fabric and PVA.
[0090] <Step of providing polymeric elastomer> The sea-free PVA-attached sheet obtained as above was immersed in a dimethylformamide (hereinafter sometimes abbreviated as DMF) solution of polyurethane (PUA, polycarbonate-based) adjusted to a solid content concentration of 11.3%, then squeezed with a roll, and the polyurethane was coagulated in an aqueous solution of DMF concentration of 30%. After that, the PVA and DMF were removed with hot water, and the sheet was dried with hot air at a temperature of 110°C for 10 minutes to obtain a polyurethane-attached sheet with a thickness of 2.4 mm and a polyurethane mass of 27% by mass relative to the mass of the fiber-entangled body.
[0091] The polyurethane-coated sheet obtained as described above was cut in half perpendicular to the thickness direction to obtain half-cut sheets having a thickness of 1.2 mm.
[0092] <Step of forming naps on both surfaces of the sheet-like material> The half-cut sheet obtained as described above, The surface formed by cutting in half (hereinafter, simply referred to as the half-cut surface) and the opposite surface (later, Side closest to fabric (The face that became the face of Grind with endless sandpaper of sandpaper size 320, Half-cut surface (later, Opposite side closer to the fabric (The face that became the face of The fabric was ground with endless sandpaper having a grit size of 180 to form a napped surface, thereby obtaining a napped sheet having a thickness of 0.9 mm.
[0093] The raised sheet obtained as described above is dyed black using a disperse dye at a temperature of 120°C using a jet dyeing machine, dried, and width-set. The half cut surface and the opposite surface (later, Side closest to fabric (The face that became the face of The result is shown in Table 1. The obtained artificial leather has an average of single Fiber diameter is 4.2μm, thickness is 1.0mm, and weight is 300g / m 2 And the side closest to the fabric Face The average nap length is 95 μm, the CV value of the nap length is 14%, the thickness of the fabric is 290 μm, and the fabric and the side close to the fabric are FaceThe distance between the surface and the surface was 170 μm. The amount of fiber waste during washing of this artificial leather was 2.0 (mg / 100 cm of artificial leather). 2 ) and there was very little fiber shedding during washing. In addition, the surface was in good condition after the abrasion test.
[0094] [Example 2] <Step of producing fiber entanglement> In the same manner as in Example 1, a sheet with sea-free PVA was obtained.
[0095] <Step of providing polymeric elastomer> The sea-free PVA-attached sheet obtained as above was immersed in a DMF (dimethylformamide) solution of polyurethane (PUB, polyether-based) adjusted to a solid content concentration of 11.3%, then squeezed with a roll, and the polyurethane was coagulated in an aqueous solution of DMF concentration of 30%. After that, the PVA and DMF were removed with hot water, and the sheet was dried for 10 minutes with hot air at a temperature of 110°C to obtain a polyurethane-attached sheet with a thickness of 2.4 mm and a polyurethane mass of 27% by mass relative to the mass of the fiber-entangled body.
[0096] The polyurethane-coated sheet obtained as described above was cut in half perpendicular to the thickness direction to obtain half-cut sheets having a thickness of 1.2 mm.
[0097] <Step of forming naps on both surfaces of the sheet-like material> An artificial leather was obtained in the same manner as in Example 1, except that the half-cut sheet obtained as described above was used. The results are shown in Table 1. The artificial leather obtained had an average of single Fiber diameter is 4.2μm, thickness is 1.0mm, and weight is 300g / m 2 And the side closest to the fabric Face The average nap length is 103 μm, the CV value of the nap length is 16%, the thickness of the fabric is 285 μm, and the fabric and the side close to the fabric are Face The distance between the surface and the surface was 167 μm. The amount of fiber waste during washing of this artificial leather was 3.2 (mg / 100 cm of artificial leather). 2 ) and there was little fiber shedding during washing. In addition, the surface was in good condition after the abrasion test.
[0098] [Example 3] <Step of producing fiber entanglement> A raw cotton for islands-in-sea type composite fibers was obtained in the same manner as in Example 1, except that polyethylene terephthalate (PET B) having an intrinsic viscosity (IV value) of 0.73, containing petroleum-derived ethylene glycol as a polymerization component, and not containing any component derived from 1,2-propanediol was used as the island component.
[0099] Next, the raw cotton of the islands-in-the-sea type composite fiber was used to form a laminated web through carding and cross-wrapping processes, and further, a plain weave fabric (weight 75 g / m) with a warp density of 95 threads / 2.54 cm and weft density of 76 threads / 2.54 cm was produced using a multifilament (average single fiber diameter: 11 μm, total fineness: 84 dtex) made of polyethylene terephthalate with an intrinsic viscosity (IV value) of 0.65 and a polymerization component of ethylene glycol derived from petroleum resources, twisted at 2500 T / m for both the weft and warp. 2 ) was laminated on the top and bottom of the laminated web, and the density was 2500 threads / cm 2 The fabric is needle punched with the number of punches, and the weight is 700g / m 2 Thus, a fiber-entangled body having a thickness of 3.0 mm was obtained.
[0100] A sheet with sea-free PVA was obtained in the same manner as in Example 1, except that the fiber-entangled body obtained as described above was used.
[0101] <Step of applying polymeric elastomer to step of forming nap on both surfaces of sheet-like material> An artificial leather was obtained in the same manner as in Example 1, except that the half-cut sheet with sea-free PVA obtained as described above was used. The results are shown in Table 1. The artificial leather obtained had an average of single Fiber diameter is 4.2μm, thickness is 1.0mm, and weight is 300g / m 2 And the side closest to the fabric Face The average nap length is 94 μm, the CV value of the nap length is 16%, the thickness of the fabric is 294 μm, and the side close to the fabric is Face The distance between the surface and the surface was 166 μm. The amount of fiber waste during washing was 2.5 mg / 100 cm of artificial leather. 2) and there was little fiber shedding during washing. In addition, the surface was in good condition after the abrasion test.
[0102] [Example 4] <Step of producing fiber entanglement body - step of providing polymer elastomer> In the same manner as in Example 1, a half-cut sheet having a thickness of 1.2 mm was obtained.
[0103] <Step of forming naps on both surfaces of the sheet-like material> The half-cut sheet obtained as described above is and the opposite side (later Surface closest to the fabric (The surface that became An artificial leather was obtained in the same manner as in Example 1, except that no shearing process was performed on the fabric. The results are shown in Table 1. The artificial leather obtained had an average of single Fiber diameter is 4.2μm, thickness is 1.0mm, and weight is 300g / m 2 And the side closest to the fabric Face The average nap length is 133 μm, the CV value of the nap length is 24%, the thickness of the fabric is 290 μm, and the fabric and the side close to the fabric are Face The distance between the surface and the surface was 170 μm. The amount of fiber waste during washing was 3.6 (mg / 100 cm of artificial leather). 2 ) and there was little fiber shedding during washing. In addition, the surface was in good condition after the abrasion test.
[0104] [Table 1]
[0105] [Comparative Example 1] <Step of producing fiber entanglement body - step of providing polymer elastomer> In the same manner as in Example 1, a half-cut sheet having a thickness of 1.2 mm was obtained.
[0106] <Step of forming naps on both surfaces of the sheet-like material> The half-cut sheet obtained as described above, The surface opposite to the half cut surface (in Example 1, Surface closest to the fabric (The surface that becameAn artificial leather was obtained in the same manner as in Example 1, except that the nap was not raised. The results are shown in Table 2. The artificial leather obtained had an average single Fiber diameter is 4.2μm, thickness is 1.0mm, and weight is 310g / m 2 The thickness of the fabric is 290 μm, and the fabric and the side close to the fabric Face The distance between the surface and the surface was 191 μm. The amount of fiber waste during washing was 7.1 (mg / 100 cm of artificial leather). 2 ) and there was a somewhat large amount of fiber shedding during washing.
[0107] [Comparative Example 2] <Step of producing fiber entanglement body - step of providing polymer elastomer> In the same manner as in Example 1, a half-cut sheet having a thickness of 1.2 mm was obtained.
[0108] The half-cut sheet obtained as described above, The surface opposite to the half cut surface (in Example 1, Surface closest to the fabric (The surface that became An artificial leather was obtained in the same manner as in Example 1, except that 0.1 mm more was ground off. The results are shown in Table 2. The average diameter of the ultrafine fibers in the obtained artificial leather was single Fiber diameter is 4.2μm, thickness is 0.90mm, and weight is 270g / m 2 And the side closest to the fabric Face The average nap length is 71 μm, the CV value of the nap length is 18%, the thickness of the fabric is 293 μm, and the fabric and the side close to the fabric are Face The distance between the surface and the surface was 71 μm. The amount of fiber waste during washing was 2.7 mg / 100 cm of artificial leather. 2 ) and although there was little fiber loss during washing, the fabric was exposed on the surface after the abrasion test, resulting in a significantly poor appearance.
[0109] [Comparative Example 3] <Step of producing fiber entanglement body - step of providing polymer elastomer> In the same manner as in Example 1, a half-cut sheet having a thickness of 1.2 mm was obtained.
[0110] <Step of forming naps on both surfaces of the sheet-like material> The half-cut sheet obtained as described above, The half-cut surface and the opposite surface (later,Surface closest to the fabric (The surface that became An artificial leather was obtained in the same manner as in Example 1, except that the surface of the ultrafine fibers was ground with endless sandpaper having a grit size of 180. The results are shown in Table 2. The artificial leather obtained had an average single Fiber diameter is 4.2μm, thickness is 1.0mm, and weight is 300g / m 2 And the side closest to the fabric Face The average nap length is 168 μm, the CV value of the nap length is 17%, the thickness of the fabric is 296 μm, and the side close to the fabric is Face The distance between the surface and the surface was 189 μm. The amount of fiber waste during washing was 7.6 (mg / 100 cm of artificial leather). 2 ) and there was a somewhat large amount of fiber shedding during washing.
[0111] [Comparative Example 4] <Step of producing fiber entanglement body - step of providing polymer elastomer> In the same manner as in Example 1, a half-cut sheet having a thickness of 1.2 mm was obtained.
[0112] <Step of forming naps on both surfaces of the sheet-like material> The half-cut sheet obtained as described above, The half-cut surface and the opposite surface (later, Surface closest to the fabric (The surface that became Grind with endless sandpaper of sandpaper size 180, and then The half-cut surface and the opposite surface (later, Surface closest to the fabric (The surface that became An artificial leather was obtained in the same manner as in Example 1, except that no shearing process was performed on the fabric. The results are shown in Table 2. The artificial leather obtained had an average of single Fiber diameter is 4.2μm, thickness is 1.0mm, and weight is 300g / m 2 And the side closest to the fabric Face The average nap length is 172 μm, the CV value of the nap length is 35%, the thickness of the fabric is 287 μm, and the side close to the fabric is Face The distance between the surface and the surface was 191 μm. The amount of fiber waste during washing was 10.4 (mg / 100 cm of artificial leather). 2 ) and a large amount of fibers were lost during washing.
[0113] [Table 2]
Claims
1. The artificial leather comprises a fiber-entangled body obtained by entangling a woven fabric with a nonwoven fabric made of ultrafine fibers having an average single fiber diameter of 1 μm or more and 10 μm or less, and a polymeric elastomer, and satisfies the following requirements (1) to (3). (1) Both surfaces of the artificial leather, one close to the woven fabric and the other opposite to the surface close to the woven fabric, are napped, and the woven fabric is not exposed on the surface of the entangled fiber body. (2) Among the surfaces having nap, the average nap length of the surface close to the woven fabric is 50 μm or more and 150 μm or less, and the CV value of the nap length is 30% or less. (3) In a cross section in the thickness direction of the artificial leather, the following formula (i) is satisfied: B>A / 2...(i) Here, A is the thickness of the fabric (μm), and B is the distance (μm) between the fabric and the surface closest to the fabric.
2. 2. The artificial leather according to claim 1, wherein the polymeric elastomer is a polycarbonate-based polyurethane.
3. 3. The artificial leather according to claim 1, wherein the nonwoven fabric is made of a polyester-based resin, and the polyester-based resin contains a component derived from 1,2-propanediol in an amount of 1 ppm or more and 500 ppm or less.
4. The artificial leather according to any one of claims 1 to 3, wherein the biomass plastic degree defined in ISO 16620 (2015) is 10% or more and 100% or less.
Citation Information
Patent Citations
Nubuck leather like sheet-shaped product and method for producing the same
JP2006241620A
Stretchable sheet and method for producing the same
JP2008261082A
Sheet-formed article, and method of producing the same
JP2017133134A
Napped artificial leather and manufacturing method therefor
WO2015045367A1
Clothing
WO2017033702A1